The integration of computer systems into the expansive field of video games - Africa, Aaron Don M. (Animo Repository, 2019)
In today’s day and age, the recent generations are the targets of video game companies. Most companies associated have goals that correspond with their target market. The companies create what the consumers want, which are video games. Everyone knows what are video games, but what are its comprised components? With that said, this research paper aims to provide information to the field of computer systems, more specifically, its integration with video games. Another objective of this paper is to give awareness of how computer systems work to give video games an extraordinary feel. This is important because individuals need to understand the various topics tackled by video games. These topics would include various computer systems like Spatial imaging, which is the ability to interact with 3D objects in a specific environment. Artificial neural networking and electronic sensors are some of the few computer systems to be tackled. The applications will be further studied so that the information on these systems can help give knowledge to people. © 2019, World Academy of Research in Science and Engineering. All rights reserved.